2020
DOI: 10.21203/rs.3.rs-19045/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Noise exposure-induced intestinal flora dysbiosis disrupts homeostasis of oxi-inflamm-barrier in the gut–brain axis of APP/PS1 mice: implications for early onset Alzheimer's disease

Abstract: Background: Environmental noise exposure and genetic risk factors are thought to be associated with gut microbiome that exacerbates Alzheimer’s disease (AD) pathology. However, the role and mechanism of environmental risk factors in early-onset AD (EOAD) pathogenesis remain unclear. Methods: We established APP/PS1 Tg and C57BL/6 (wild type [WT]) mouse models to evaluate the molecular pathways underlying EOAD pathophysiology following environmental noise exposure. 16S rRNA sequencing analyses were used for inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…A recent mouse-model study demonstrated adverse effects of noise pollution on the gut microbiome (Cui et al, 2020). They used 16S rRNA sequencing to characterize the gut microbiome and the Tax4Fun package in R to predict metagenome content.…”
Section: The Effects Of Anthropogenic Sound Exposure On Microorganisms Bacteriamentioning
confidence: 99%
“…A recent mouse-model study demonstrated adverse effects of noise pollution on the gut microbiome (Cui et al, 2020). They used 16S rRNA sequencing to characterize the gut microbiome and the Tax4Fun package in R to predict metagenome content.…”
Section: The Effects Of Anthropogenic Sound Exposure On Microorganisms Bacteriamentioning
confidence: 99%
“…recent mouse-model study demonstrated adverse effects of noise pollution on the gut microbiome(Cui et al 2020). They used 16S rRNA sequencing to characterise the gut microbiome and the Tax4Fun package in R to predict metagenome content.…”
mentioning
confidence: 99%